INCREASING THE WELFARE OF THE CIVIL SOCIETY THROUGH THE RECYCLE OF WASTE CASHEW - Mei Indrawati; Dwi Lesno Panglipursari; Rachmat Hidayat Kurniawan (Asian Journal of Innovation and Entrepreneurship, 2017)
The program is implemented in the Dasuk County in Sumenep Regency with two goals major producer of cashew Beringin village and Jilbudan village. The program IBW has a purpose: 1) to increase welfare better society through the utilization of local resources that have economic value, 2) increasing the skills and professionalism of people, 3) increase the capacity of cashew farming communities to diversifying the product, 4) the formation of economic business community and institutions that are structured to cashew farmers. The project used two approaches, Training and mentoring approach. Training approach include: 1) entrepreneurial training; 2) skills training for women and youth based on local resources; 3) training appearance and diversifying the cultivation of cashew products professionally and 4) marketing training through the web and on-line. While this method of assistance include: 1) facilitation of technology transfer for the production of cashew cultivation; 2) facilitation of technology transfer diversifying cashew products in a professional manner; 3) mentoring network strengthening marketing activities and 4) institutional strengthening assistance. Expected outcomes of this program for the second year of this is establishing erpreneurship on society, increasing the skills of women and youth with the waste cashew shell, processed products jam and candied cashews, waste cashew to feed the livestock through several processes of ensiling, the manufacture of the product label and cashew packaging technology products, the establishment of farmer networks